(untitled) (REM. Chilean Journal of Musical Education, 2025)
The purpose of this article is to outline the methods of pedagogical learning adopted by a music teacher who made use of musical scores in her piano lessons so that a student with cerebral palsy could attend the classes. This means the method of teaching the piano can still follow a traditionalist approach that fully recognises the view that learning the instrument requires “talent”. This traditional standpoint is often restricted to the inclusion of new methods, while failing to take account of those who “lack talent” or are handicapped. The study which adopts a qualitative approach, is a passage taken from a more wide-ranging research project which examines the kinds of adjustments required for both teaching and learning the piano within a culture of inclusion. Those carried out by the teacher are linked to creative learning which requires the teacher to employ creative strategies to make the learning more effective. The outcome of the research showed in what ways the materials were adapted to ensure the student could learn how to play the piano, and this was reflected in his motivation to play the instrument as well as making clear the extent of his desire to spend more time studying to achieve further progress. This experience meant that the teacher could reconsider her practice with other students by adapting the materials to the needs of each individual so that they could all feel encouraged to improve their learning of the instrument.